IDENTIFIKASI BAKTERI YANG MENGONTAMINASI KONSENTRAT TROMBOSIT - Dewi Astuti; Eva Ayu Maharani (Poltekkes Kemenkes Jakarta III, 2014)
Indonesian Red Cross (IRC) is an organization that received an assignment to provide blood for transfusion therapy. Blood for transfusion should free from infectious disease. Several studies have shown that viruses, bacteria and protozoa can be transmitted by transfusion. Clinical features due to bacterial contamination varies from asymptomatic, mild fever, acute sepsis, hypotension and can even cause death. Components of platelet concentrates can be a good place for the growth of Gram positive and Gram negative bacteria, because it is stored at a temperature of 20O-24OC with the addition of dextrose that can be used as an energy source for bacteria. Bacteria identification performed by culturing the component of platelet concentrates on BPA tube of Bact / ALERT. Tube with contaminated bacteria is subcultured onto blood agar media. Bacterial colonies from blood agar stained with Gram staining and further identified using API20E, API 20NE, API 20STREP, MSA media or staphilase test using reagents Staphaurex*, according to the type of bacteria detected on Gram stain. The results shown a component of platelet concentrates is contaminated by bacteria., The bacteria is Gram positive cocci clusters. MSA and staphilase test have a negative result, so it can be concluded that the bacteria that had contaminated platelet concentrates is Staphylococcus epidermidis.